Masjid Kampung Hulu, Melaka - Azam Mohamad; Amani Azhari; Norlina Hassan; Noraiza Darus; Shaikh Ahmad Jafni Sk Abdullah; Mohd. Rosli Suffi; Som Chai Eh Suk (Sekudai : UTM, 1988)
Kajian Lukisan Terukur (Jabatan Senibina) - Universiti Teknologi Malaysia, 1988